Whole genome sequencing and mutation rate analysis of trios with paternal dioxin exposure. Issue 10 (16th July 2018) - Ton, Nguyen Dang; Nakagawa, Hidewaki; Ha, Nguyen Hai; Duong, Nguyen Thuy; Nhung, Vu Phuong; Hien, Le Thi Thu; Hue, Huynh Thi Thu; Hoang, Nguyen Huy; Wong, Jing Hao; Nakano, Kaoru; Maejima, Kazuhiro; Sasaki‐Oku, Aya; et al.
Abstract: 2, 3, 7, 8‐Tetrachlorodibenzo‐ p ‐dioxin (TCDD) or dioxin, is commonly considered the most toxic man‐made substance. Dioxin exposure impacts human health and diseases, birth defects and teratogenesis were frequently observed in children of persons who have been exposed to dioxin. However, the impact of dioxin on human mutation rate in trios has not yet been elucidated at the whole genome level. To identify and characterize the genetic alterations in the individuals exposed to dioxin, we performed whole genome sequencing (WGS) of nine Vietnamese trios whose fathers were exposed to dioxin. In total, 846 de novo point mutations, 26 de novo insertions and deletions, 4 de novo structural variations, and 1 de novo copy number variation were identified. The number of point mutations and dioxin concentrations were positively correlated ( P ‐value < 0.05). Considering the substitution pattern, the number of A > T/T > A mutation and the dioxin concentration was positively correlated ( P ‐value < 0.05). Our analysis also identified one possible disease‐related mutation in LAMA5 in one trio. These findings suggested that dioxin exposure might affect father genomes of trios leading to de novo mutations in their children. Further analysis with larger sample sizes would be required to better clarify mutation rates and substitution patterns in trios caused by dioxin. Abstract : To identify and characterize the genetic alterations in the individuals exposed to dioxin, we performed whole genome sequencing of nine Vietnamese trios whose fathers were exposed to dioxin. In total, 846 de novo SNVs, 26 de novo indels, 4 de novo SVs, and 1 de novo CNV were identified. The number of point mutations and dioxin concentrations were positively correlated. Considering the substitution pattern, the number of A > T/T > A mutation and the dioxin concentration was positively correlated.